2018
DOI: 10.1177/1744806918807050
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/NF-κB signaling activation in plantar tissue and dorsal root ganglion involves in the development of postoperative pain

Abstract: BackgroundSevere postoperative pain remains a clinical problem that impacts patient’s rehabilitation. The present work aims to investigate the role of Toll-like receptor-4 (TLR4) activation in wounded plantar tissue and dorsal root ganglion (DRG) in the genesis of postoperative pain and its underlying mechanisms.ResultsPostoperative pain was induced by plantar incision in rat hind paw. Plantar incision led to increased expression of TLR4 in ipsilateral lumbar 4–5 (L4/L5) DRGs, which occurred at 2 h and was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Previous studies have also reported that the inhibition of the NF-κB signaling pathway can protect against IVD degeneration (40,41). It is well known that the TLR4/NF-κB signaling pathway mediates inflammation cascades to amplify the inflammatory response (42,43). In this study, the levels of TNF-α, IL-1β and IL-6 were markedly lower in the LPS + inhibitor group than that in the LPS-stimulated NP cells, while miR-222 mimics enhanced the production of TNF-α, IL-1β and IL-6, in comparison to the LPS group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that the inhibition of the NF-κB signaling pathway can protect against IVD degeneration (40,41). It is well known that the TLR4/NF-κB signaling pathway mediates inflammation cascades to amplify the inflammatory response (42,43). In this study, the levels of TNF-α, IL-1β and IL-6 were markedly lower in the LPS + inhibitor group than that in the LPS-stimulated NP cells, while miR-222 mimics enhanced the production of TNF-α, IL-1β and IL-6, in comparison to the LPS group.…”
Section: Discussionmentioning
confidence: 99%
“…Some animals underwent stereotaxic implantation of an ipsilateral hippocampal depth or surface electrode 25 days or 85 days after FPI or sham injury. Drug dosing was based on published studies in vivo …”
Section: Methodsmentioning
confidence: 99%
“…Drug dosing was based on published studies in vivo. [20][21][22][23] Electrophysiology Six to 8 days after FPI or sham injury, rats were anesthetized with isoflurane and decapitated. Horizontal brain slices (400μm for field recordings and 350μm for whole cell recordings) were prepared as described previously.…”
Section: Drug Administration and Electrode Implantationmentioning
confidence: 99%
“…Other groups further demonstrated that inhibition of IL-1β signaling through antagonism of its receptor significantly decreased postoperative pain-like behavior in rodents (32, 98, 100). Furthermore, additional research has established that inhibition of the upstream mediators of IL-1β, such as TLR4 (98, 103), NF-κB (103), caspase-1 (104), or NLRP3 (13), decreases postoperative pain-like behaviors in rodents. General blockade of IL-1β signaling, like that obtained with FDA approved Anakinra (IL-1R1 antagonist), increases the rate of infections due to the necessity of IL-1β for bacterial infection clearance (105, 106).…”
Section: Proinflammatory Il-1β and Postoperative Painmentioning
confidence: 99%